MOTIVATION MODEL-BASED COMMUNICATION SYSTEM E-LEARNING - Eriek Orlando (JAKSTIK Journal, 2005)
ELearning System is a solution that is needed in the era of globalization of education today.The presence of eLearning with the support of information technology to bring the influenceof conventional education in the transformation process into digital form, both in content andsystem. Today eLearning industry is experiencing a crisis, which resulted in the failure of theimplementation of eLearning in various sectors in the world. The failure was mainly due tovery few users and are not motivated to finish until the end of eLearning materials. Writingprovides a solution by developing a model-based eLearning system that can motivate thecommunity to overcome the low motivated users and not users in using the eLearning system.Community motivation model developed based on theories of learning and motivation theorycapturing requirements in the field of requirements engineering. Measurement of theeffectiveness of community motivation model using statistical indicators of visits, trafficranking, comparison with similar eLearning system, and relationships between concepts inthe model. The model developed has also been applied in a public web based eLearningsystem IlmuKomputer.Com, with a significant result.